An Oral Salmonella-Based Vaccine Inhibits Liver Metastases by Promoting Tumor-Specific T-Cell-Mediated Immunity in Celiac and Portal Lymph Nodes: A Preclinical Study - Vendrell, Alejandrina; Mongini, Claudia; Gravisaco, María José; Canellada, Andrea; Tesone, Agustina Inés; Goin, Juan Carlos; Waldner, Claudia Inés (Frontiers in Immunology, 2016)
Primary tumor excision is one of the therapies of cancer most widely used. However, the risk of metastases development still exists following tumor resection. The liver is a common site of metastatic disease for numerous cancers. Breast cancer is one of the most frequent source of metastases to the liver. The aim of this work was to evaluate the efficacy of the orally-administered Salmonella Typhi vaccine strain CVD 915 on the development of liver metastases in a mouse model of breast cancer. To this end, one group of BALB/c mice was immunized with CVD 915 via o.g. while another received PBS as a control. After 24 h, mice were injected with LM3 mammary adenocarcinoma cells into the spleen and subjected to splenectomy. This oral Salmonella-based vaccine produced an antitumor effect, leading to a decrease in the number and volume of liver metastases. Immunization with Salmonella induced an early cellular immune response in mice. This innate stimulation rendered a large production of IFN-γ by intrahepatic immune cells (IHIC) detected within 24 h. An antitumor adaptive immunity was found in the liver and celiac & portal lymph nodes (LDLN) 21 days after oral bacterial inoculation. The antitumor immune response inside the liver was associated with increased CD4+ and DC cell populations as well as with an inflammatory infiltrate located around liver metastatic nodules. Enlarged levels of inflammatory cytokines (IFN-γ and TNF) were also detected in IHIC. Furthermore, a tumor-specific production of IFN-γ and TNF as well as tumor-specific IFN-γ-producing CD8 T cells (CD8+IFN-γ+) were found in the celiac & portal lymph nodes of Salmonella-treated mice. This study provides first evidence for the involvement of LDLN in the development of an efficient cellular immune response against hepatic tumors, which resulted in the elimination of liver metastases after oral Salmonella-based vaccination.